Reconstruction of Distal Nasal Defects Using Free Cartilage Batten Grafting With Secondary Intention Healing: A Retrospective Case Series of 129 Patients. Issue 1 (January 2021) - Kim, Dong Joo; Makdisi, Joy; Regan, Christina; Chen, Pin-Chun; Chao, Elizabeth; Rotunda, Adam M.
Abstract : BACKGROUND: Surgical defects of the distal nose can pose significant reconstructive challenges. Free cartilage batten graft (FCBG) with secondary intention healing is an underreported yet effective repair option with cosmetically and functionally satisfying outcomes. OBJECTIVE: To share the authors' experience using FCBG with secondary intention healing on multiple nasal subunits, including a detailed evaluation of wound/graft characteristics and design modifications to optimize success with this single-stage approach. METHODS: A retrospective study of 129 patients who underwent FCBG with secondary intention healing after Mohs surgery from 2011 to 2018, using statistical analysis of numerous outcome measures graded independently by 2 fellowship-trained Mohs surgeons. RESULTS: Overall, healed wounds were graded aesthetically as follows: excellent (24%), very good (31%), good (31%), or poor (14%). Excellent/very good outcomes were seen for superficial ( p < .001), small-to-medium sized wounds ( p < .0001) repaired with cartilage that closely approximated the defect size ( p < .05). Consistently optimal outcomes were seen in the 19 repairs involving the alar lobule (mid-ala) alone, graded excellent (47%), very good (32%), and good (21%). A majority of patients (86%) experienced mild to no alar retraction. Although 67% of all patients had some skin surface contour irregularity, only 8% of patients sought dermabrasion. Neither hematoma, infection, ear deformity, chondritis, nor graft desiccation were reported. CONCLUSION: A modified approach to FCBG with secondary intention healing provides a reliable, minimalistic, low-risk reconstructive option for mid-alar defects. Abstract : Supplemental Digital Content is Available in the Text.